2020
DOI: 10.1021/acs.jnatprod.0c00587
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Chromones and Benzoxepines from the Leaves of Ptaeroxylon obliquum

Abstract: This study reports the first total synthesis of the bioactive oxepinochromones 12-O-acetyleranthin (8) (angular isomer) and 12-Oacetylptaeroxylinol (9) (linear isomer). The antifungal activity of these compounds and their derivatives was determined against Candida albicans and Cryptococcus neoformans. Most compounds had good selectivity between the two fungi and showed moderate to good activity. 12-O-Acetyleranthin ( 8) had the highest activity against C. albicans, with an MIC value of 9.9 μM, while 12-O-acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
(114 reference statements)
2
20
0
Order By: Relevance
“…[ 68 ] The compound has previously been synthesized through oxa‐Michael cyclization of a prenylated chalcone [ 17 ] and via regioselective enzyme catalyzed prenylation of eriodictyol. [ 69 ] Our synthesis started with the known compounds 9c [ 70 ] and 10e , [ 71 ] which were reacted in a Claisen‐Schmidt condensation under the previously established conditions to furnish 11ce . Microwave promoted tandem Claisen‐rearrangement/6‐endo‐cyclization of 11ce gave a separable mixture of MOM‐protected flavanone 12ce and uncyclized chalcone 13ce in a combined yield of 67 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 68 ] The compound has previously been synthesized through oxa‐Michael cyclization of a prenylated chalcone [ 17 ] and via regioselective enzyme catalyzed prenylation of eriodictyol. [ 69 ] Our synthesis started with the known compounds 9c [ 70 ] and 10e , [ 71 ] which were reacted in a Claisen‐Schmidt condensation under the previously established conditions to furnish 11ce . Microwave promoted tandem Claisen‐rearrangement/6‐endo‐cyclization of 11ce gave a separable mixture of MOM‐protected flavanone 12ce and uncyclized chalcone 13ce in a combined yield of 67 %.…”
Section: Resultsmentioning
confidence: 99%
“…Microwave reactions were carried out in an Anton‐Paar‐monowave‐300 or an Anton‐Paar‐monowave‐400 reactor (monowave, maximum power 850 W, temperature control by IR‐sensor, vial volume 20 mL). These starting materials were synthesized following literature procedures: 9a , [ 20 ] 9b , [ 22 ] 9c [ 70 ] and 10e . [ 71 ]…”
Section: Methodsmentioning
confidence: 99%
“…Generally, these procedures involve a high atom economy and in most of the cases allow multiple‐bond forming transformations (MBFTs) under mild reaction conditions [2] . In particular, 4 H ‐chromenes are oxa‐heterocyclic compounds with a remarkable role in medicinal chemistry and drug discovery due to their broad spectrum of biological activities, including antimicrobial, [3] anti‐inflammatory, [4] antibacterial, [5] anticancer, [6] antifungal, [7] among others [8] . In this regard, MCRs have gained considerable attention for assembling structurally diverse 4 H ‐chromenes in a rapid, step‐economic, and eco‐friendly manner [9] .…”
Section: Introductionmentioning
confidence: 99%
“…As early as the late 19th century, Khellin was extracted from the fruit of the Umbellifera, which was widely distributed in eastern Mediterranean countries, and was used as the first chromone drug in clinical applications [ 5 ]. Meanwhile, biological activity results showed that both natural and synthetic chromone compounds had a wide range of biological activities, such as antifungal [ 6 , 7 ], antibacterial [ 6 ], anticancer [ 8 ], and antiviral [ 9 ] activity. Thiochromanone, a kind of chromone compound, is an important substance in the synthesis of various active molecules that are extensively used in the intermediate skeleton of drugs and has attracted more and more attention due to their extensive biological activities, including antiviral [ 10 ], antibacterial [ 11 , 12 ], antifungal [ 11 , 13 , 14 , 15 ], herbicidal [ 16 , 17 ], and insecticidal [ 18 ] activity.…”
Section: Introductionmentioning
confidence: 99%